Separating Long‐Term and Short‐Term Mass Changes of Antarctic Ice Drainage Basins: A Coupled State Space Analysis of Satellite Observations and Model Products. Issue 6 (18th June 2021) - Willen, M. O.; Broerse, T.; Groh, A.; Wouters, B.; Kuipers Munneke, P.; Horwath, M.; van den Broeke, M. R.; Schröder, L.
Abstract: Satellite gravimetry and altimetry measurements record gravity and elevation changes, respectively, which are useful for determining mass and volume change of the Antarctic Ice Sheet. Common methods employ products from regional climate modeling and firn modeling to aid interpretation and to link volume changes to mass changes. Estimating deterministic parameters over defined time periods is a conventional way to evaluate those changes. To overcome limitations of deterministic analyses with respect to time‐variable signals, we have developed a state‐space model framework. Therein, we jointly evaluate four mass and volume data sets by coupling of temporal signal variations. We identify long‐term signals of ice drainage basins that are observed by the satellite gravimetry mission GRACE and several satellite altimetry missions from April 2002 until August 2016. The degree to which we can separate long‐term and short‐term variations strongly depends on the similarity of the mass and volume change time series. For the drainage system of the Pine Island Glacier (West Antarctica), our results show noticeable variations of the long‐term trend with an acceleration of the contribution of ice dynamics to the mass balance from −11 ± 8 to −58 ± 8 Gt a −1 . Our results in Dronning Maud Land (East Antarctica) show a positive long‐term contribution to the mass balance at almost a constant rate. The presented approach can fit time‐variable changes without artificial selection of periods of interest. Furthermore, because we only enforce common long‐term time variations between mass and volume data, differences in mean trend rates help to uncover model discrepancies. Plain Language Summary: The ice sheet in Antarctica is constantly changing in volume and mass. Overall, the ice sheet is shrinking, but there are regions with large losses and regions with small mass gains. Mass loss can be caused either by faster flow of ice into the ocean (ice‐dynamical change) or by less snowfall (surface climate). We aim to separate these two processes. GRACE satellites measure the changes in the gravity field of the Earth caused by mass changes. Other satellites that carry an altimeter can measure the volume changes of the ice sheet by recording changes in ice surface elevation. The surface climate can be simulated by a regional climate model for Antarctica. We combine these sources of information to extract long‐term signals of mass change and find they are mainly due to ice dynamics. As an advantage over earlier methods, the change of our long‐term signal does not have to be constant in time. We show that there is an accelerated ice‐dynamical mass loss in the glacier drainage basins of West Antarctica. In contrast, we identify almost constant rates of the trend in drainage basins in East Antarctica. Key Points: We have developed a state space filter framework to simultaneously evaluate GRACE and altimetry data, with climate and firn model products This approach allows the estimation of time‐variable mass and volume changes of Antarctic ice drainage basins We identify the long‐term trend of Antarctic ice drainage basins, which is presumably linked to variations in ice dynamics